The importance of clinical history in suspected otosclerosis: a case report. (3rd April 2018) - Tulli, Michele; Gatti, Omar; Galli, Andrea; Ferraro, Milena; Di Santo, Davide; Piccioni, Lucia Oriella
Abstract: Isolated malleus handle fracture (IMHF) is a lesser-known pathology. Its subtle and non-pathognomonic clinical characteristics mean its diagnosis is often overlooked. We describe a case of conductive hearing loss brought to our attention with a suspected diagnosis of otosclerosis. We describe the diagnostic workup and management of the patient. We underline the importance of performing a thorough and appropriate clinical exam, the value of computer tomography (CT) reconstruction and above all, an accurate anamnesis regarding the onset of the symptomatology in order to consider isolated fracture of the malleus amongst the possible differential diagnoses.